Two distinct loci affecting conversion to mucoidy in Pseudomonas aeruginosa in cystic fibrosis encode homologs of the serine protease HtrA. - Boucher, J C (1996)
Conversion to a mucoid, exopolysaccharide alginate-overproducing phenotype in Pseudomonas aeruginosa is associated with chronic respiratory infections in cystic fibrosis. Mucoidy is caused by muc mutations that derepress the alternative sigma factor AlgU, which in turn activates alginate biosynthetic and ancillary regulatory genes. Here we report the molecular characterization of two newly identified genes, algW and mucD, that affect expression of mucoidy. The algW gene, mapping at 69 min, was isolated on the basis of its ability to suppress mucoidy and reduce transcription of the alginate biosynthetic gene algD. The predicted primary structure of AlgW displayed similarity to HtrA (DegP), a serine protease involved in proteolysis of abnormal proteins and required for resistance to oxidative and heat stress in enteric bacteria. Inactivation of algW on the chromosome of the wild-type nonmucoid strain PAO1 caused increased sensitivity to heat, H2O2, and paraquat, a redox cycling compound inducing intracellular levels of superoxide. This mutation also permitted significant induction of alginate production in the presence of subinhibitory concentrations of paraquat. Two new genes, mucC and mucD, were identified immediately downstream of the previously characterized portion (algU mucA mucB) of the gene cluster at 67.5 min encoding the alternative sigma factor AlgU and its regulators. Interestingly, the predicted gene product of mucD also showed similarities to HtrA. Inactivation of mucD on the PAO1 chromosome resulted in conversion to the mucoid phenotype. The mutation in mucD also caused increased sensitivity to H2O2 and heat killing. However, in contrast to algW mutants, no increase in susceptibility to paraquat was observed in mucD mutants. These findings indicate that algW and mucD play partially overlapping but distinct roles in P. aeruginosa resistance to reactive oxygen intermediates and heat. In addition, since mutations in mucD and algW cause conversion to mucoidy or lower the threshold for its induction by reactive oxygen intermediates, these factors may repress alginate synthesis either directly by acting on AlgU or its regulators or indirectly by removing physiological signals that may activate this stress response system.